EVALUATION OF STUDENTS' HOME STUDY HABITS IN TERMS OF TEACHER AND PARENT OPINIONS DURING THE PANDEMIC PROCESS - Kazu, Hilal; Yıldız, Fatma (Behçet ORAL, 2022)
The purpose of this research is to examine how the pandemic period influences study habits at home, in accordance with the perceptions of parents and teachers. The research group comprises 18 teachers teaching the first and second classes in the 2019-2020 academic year in a primary school in the Kangal District of Sivas province and 21 parents whose students are studying in the second grade in the same year. In this investigation, the phenomenological design, which is one of the qualitative research approaches, was applied. A descriptive analysis method was employed in the study of the data. As an outcome of the research, all of the teachers who participated claimed that they experienced challenges in acquiring the behavior of studying at home during the pandemic process. As a consequence of the teachers' judgments, it was concluded that distance education, which commenced with the epidemic phase, is not viable for the primary school level. During the epidemic period, the majority of parents reported that their adolescents struggled with motivation in their home study activities. Most of the parents indicated that assignments are required in online classroom learning. Furthermore, most parents believed that the home study habits developed during the outbreak would last long after the pandemic.

Bu çalışmanın amacı, pandemi döneminin öğrencilerin evde ders çalışma alışkanlıklarını ne şekilde etkilediğini veli ve öğretmen görüşleri doğrultusunda değerlendirmektir. Çalışma grubu, Sivas ili Kangal ilçesindeki bir ilkokulda 2019-2020 öğretim yılında birinci ve ikinci sınıfları okutan 18 öğretmen ve aynı yıl öğrencileri ikinci sınıfta okuyan 21 veliden oluşmaktadır. Bu çalışmada nitel araştırma yöntemlerinden olan olgu bilim (fenomenoloji) deseni kullanılmıştır. Verilerin analizinde betimsel analiz yöntemi kullanılmıştır. Çalışma sonucunda, katılımcı öğretmenlerin tamamı pandemi sürecinde evde ders çalışma alışkanlığı kazandırmada sorun yaşadığını belirtmiştir. Öğretmenlerin görüşleri sonucunda, pandemi süreci ile birlikte başlayan uzaktan eğitimin ilkokul düzeyine uygun olmadığı belirlenmiştir. Velilerin geneli pandemi sürecinde evde ders çalışma uygulamalarında çocuklarının motivasyon sıkıntısı yaşadıklarını düşünmektedirler. Velilerin büyük çoğunluğu uzaktan eğitim sürecinde ödevlerin gerekli olduğunu belirtmişlerdir. Ayrıca velilerin büyük kısmı pandemi sürecinde kazanılan evde ders çalışma alışkanlıklarının pandemi sonrasında da kalıcı olacağını düşünmektedirler.
Pandemi Sürecinde Öğrencilerin Evde Ders Çalışma Alışkanlıklarının Öğretmen ve Veli Görüşleri Açısından Değerlendirilmesi
Keywords: Other Fields of Education; Alan Eğitimleri